2013
DOI: 10.1177/0003122413484151
|View full text |Cite
|
Sign up to set email alerts
|

Does Specialization Explain Marriage Penalties and Premiums?

Abstract: Married men’s wage premium is often attributed to within-household specialization: men can devote more effort to wage-earning when their wives assume responsibility for household labor. We provide a comprehensive evaluation of the specialization hypothesis, arguing that, if specialization causes the male marriage premium, married women should experience wage losses. Furthermore, specialization by married parents should augment the motherhood penalty and the fatherhood premium for married as compared to unmarri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
191
1
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(224 citation statements)
references
References 36 publications
10
191
1
22
Order By: Relevance
“…We also find a small wage premium (0.5%) for married women (or wage penalty for single women), which is mainly driven by the for-profit sector (1%). This is consistent with recent studies showing a wage premium for marriage (even for women; for example, Dougherty, 2006;Glauber, 2007;Killewald & Gough, 2013), although the debate between a wage premium and penalty for married women is hardly settled (Loughran & Zissimopoulos, 2009, for example, find a wage penalty).…”
Section: Gender Race and Relationship Pay Differentials Between Secsupporting
confidence: 91%
“…We also find a small wage premium (0.5%) for married women (or wage penalty for single women), which is mainly driven by the for-profit sector (1%). This is consistent with recent studies showing a wage premium for marriage (even for women; for example, Dougherty, 2006;Glauber, 2007;Killewald & Gough, 2013), although the debate between a wage premium and penalty for married women is hardly settled (Loughran & Zissimopoulos, 2009, for example, find a wage penalty).…”
Section: Gender Race and Relationship Pay Differentials Between Secsupporting
confidence: 91%
“…This category includes women who may have been cohabiting. This is reasonable in this data because in a recent study using the same data set, Killewald and Gough (2013) found that the association between parenthood and wages did not differ for cohabiters compared to single people. Additionally, during the period in which these women are having first births, births to single, non-cohabiting mothers remained much more common than births to cohabiting mothers (Manning, Brown, and Stykes 2015).…”
Section: Control Variablessupporting
confidence: 77%
“…Lundberg and Rose (2000) find some evidence for negative selection of motherhood on this basis. Yet a recent paper by Killewald and Gough (2013) finds no evidence of wage anticipation effects prior to birth in the United States. If anticipation effects exist, birth spacing will affect the motherhood penalty inasmuch as it is related to women's individual capacity for productivity or their lower labor market position.…”
Section: Selectionmentioning
confidence: 97%
“…Also, the models (such as seemingly unrelated regressions or clustered standard errors), whilst accounting for interdependence, did not model how partners' outcomes were interrelated (e.g. Killewald & Gough, 2013). If the cross-partner influence was modelled in the fixed part, it was depicted as a uni-directional influence with the direction of causality running from the partner to the respondent (e.g.…”
Section: Past Analytical Approaches To the Division Of Labourmentioning
confidence: 99%